1999
DOI: 10.1116/1.590556
|View full text |Cite
|
Sign up to set email alerts
|

Electron field emission from a patterned diamondlike carbon flat cathode

Abstract: Electron field emission from a patterned diamond-like carbon flat thin film using a Ti interfacial layer A 300-nm-thick diamondlike carbon ͑DLC͒ film was deposited on to a heavily doped n-type Si ͑111͒ wafer by filtered arc deposition. A flat thin film cylindrical emitter array was then fabricated by reactive-ion etching the DLC film. Its electron field emission properties were studied using a simple diode structure. A field emission current of 0.1 A was detected under an electric field of 5.2 V/m. As large as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…6 The plasma produced by the vacuum cathodic arc were focused to pass through a curved magnetic field of a solenoid, to filter out all the neutral atoms and microparticles before deposition. A zinc target with purity of 99.99% was cleaned in acetone and alcohol ultrasonic baths, respectively, before it was fixed into the system.…”
Section: Methodsmentioning
confidence: 99%
“…6 The plasma produced by the vacuum cathodic arc were focused to pass through a curved magnetic field of a solenoid, to filter out all the neutral atoms and microparticles before deposition. A zinc target with purity of 99.99% was cleaned in acetone and alcohol ultrasonic baths, respectively, before it was fixed into the system.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some researchers have found that the crater region on diamond and DLC films created by a vacuum-arc discharge during field emission showed good emission properties. 4,5 When a critical electric field is reached, electrons impinging onto the anode produce ions that, in turn, are accelerated toward the cathode. The cathode material evaporates and is ionized by the electrons in front of the cathode, which then gives rise to an arc.…”
Section: Introductionmentioning
confidence: 99%